PENGARUH GCG DAN FIRM SIZE TERHADAP PERUSAHAAN YANG MENGALAMI FINANCIAL DISTRESS - Fidyaningrum, Alifiyah; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of good corporate governance and firm size to companies which experience financial distress.The population of this research is all manufacturing companies which arelisted in Indonesia Stock Exchange (IDX) in 2013-2015 periods, and 145 companies have been selected as samples. The research sampleshave beenselected by using purposive sampling method in accordance with the predetermined sample selection criteria 19 companies in 2013-2015 have been selected as samples so that there are 57 companies will be analyzed. This researchhas been done by using logistic regression method. The result of the research shows there none of the variables whichgive significant influence to the companies which experience financial distress. The good corporate governance mechanism is used only as the formality so itis unable to predict the companieswhich experience financial distress, in this case the mechanism should have good corporate governance of the company is required to be improved in order not to be regarded as the formality. Moreover,when the size of the company is small;, the company is prompt to experience financial distress due to lack of investors and borrowers, so that companies are required to increase the numbers of its assets in order to have the large size company and keep it away from financial distress because it is considered unable to pay liabilities of the company.Keywords: good corporate governance, firm size, financial distress.